1998
DOI: 10.1095/biolreprod59.3.676
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Secretion into Third-Ventricle Cerebrospinal Fluid of Cattle: Correspondence with the Tonic and Surge Release of Luteinizing Hormone and Its Tonic Inhibition by Suckling and Neuropeptide Y1

Abstract: Objectives of the current studies were to characterize the pattern of GnRH secretion in the cerebrospinal fluid of the bovine third ventricle, determine its correspondence with the tonic and surge release of LH in ovariectomized cows, and examine the dynamics of GnRH pulse generator activity in response to known modulators of LH release (suckling; neuropeptide Y [NPY]). In ovariectomized cows, both tonic release patterns and estradiol-induced surges of GnRH and LH were highly correlated (0.95; p < 0.01). Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 33 publications
6
59
1
6
Order By: Relevance
“…An in vivo study in cows showed that injection of NPY into the third cerebroventricle of ovariectomized cows, caused a decrease in amplitude of tonic LH secretion [94]. Another study of the same group revealed that NPY affected LH pulsatility in a dose-dependent manner, accompanied by changes in the concentration of GnRH in cerebrospinal fluid (CSF) [41].…”
Section: Regulation Of Gonadotrophinsmentioning
confidence: 99%
“…An in vivo study in cows showed that injection of NPY into the third cerebroventricle of ovariectomized cows, caused a decrease in amplitude of tonic LH secretion [94]. Another study of the same group revealed that NPY affected LH pulsatility in a dose-dependent manner, accompanied by changes in the concentration of GnRH in cerebrospinal fluid (CSF) [41].…”
Section: Regulation Of Gonadotrophinsmentioning
confidence: 99%
“…From these portal veins, pituitary capillaries emerge and the GnRH is released in the intercellular space and reaches anterior pituitary cells. GnRH concentration in the portal veins varies between 4-100pg/ml (Caraty et al, 1982;Clarke and Cummins, 1982;Levine et al, 1982;Irvine and Alexander, 1987;Gazal et al, 1998), which gives a very small amount of GnRH for the small blood volume considered. Thus, the amount of GnRH that passes in the general circulation is very small; the concentration is well below the detection threshold of known hormonal assays.…”
Section: Evolution Of Gonadotropin Secretion In the Pre-pubertal Periodmentioning
confidence: 99%
“…Due to its small peptidic structure, circulating endopeptidases degrades rapidly the GnRH. Therefore to assess the GnRH secretion, blood should be punctured from pituitary portal vessels or from canulae inserted in the third ventricle (Gazal et al, 1998) and this can only be performed in large animals and requires invasive surgical procedures (Clarke and Cummins, 1982;Levine et al, 1982). An alternative is to follow LH secretion since it has been clearly demonstrated that a GnRH pulse precedes every LH pulse (Clarke and Cummins, 1982;Caraty et al, 1989).…”
Section: Evolution Of Gonadotropin Secretion In the Pre-pubertal Periodmentioning
confidence: 99%
“…Esse peptídeo possui um padrão elevado de expressão no hipotálamo e na hipófise anterior de bovinos, sendo encontrado no corpo celular e em terminações nervosas de diversas áreas do cérebro, principalmente naquelas relacionadas com a regulação do consumo alimentar e o balanço energético (THOMAS et al, 1999). A administração central de NPY em ratos induz hiperfagia (STANLEY et al, 1986) e, em bovinos, inibe a liberação de GnRH e LH sem alterar os níveis plasmáticos de FSH (GAZAL et al, 1998). Além disso, a administração central de altas concentrações de NPY em ovelhas bloqueia completamente o pico pré-ovulatório de GnRH (ESTRADA et al, 2003).…”
Section: Introductionunclassified
“…No entanto, apesar da leptina ser capaz de reduzir a síntese e secreção de NPY (SAHU, 1998), ela não é capaz de atenuar os efeitos sobre a liberação do LH, quando esse neurotransmissor é injetado diretamente no SNC de vacas ovariectomizadas (GARCIA et al, 2004), sugerindo que, em bovinos, a leptina controla apenas as ações pré-secretórias do NPY. Ainda, parece que o NPY é capaz de controlar a liberação do LH na hipófise bovina, pois, após a infusão desse peptídeo diretamente no terceiro ventrículo hipotalâmico, a liberação do LH permaneceu totalmente bloqueada, mesmo após a pulsatilidade do GnRH estar restabelecida (GAZAL et al, 1998). Além de uma regulação na síntese de GnRH, foi demonstrado em camundongos que a leptina altera o potencial de resposta dos gonadotrofos frente ao estímulo do GnRH, através de um aumento da expressão de canais de Ca ++ (AVELINO-CRUZ et al, 2009).…”
Section: Introductionunclassified